Coke oven gas to methanol process integrated with CO2 recycle for high energy efficiency, economic benefits and low emissions. (1st February 2017) - Gong, Min-hui; Yi, Qun; Huang, Yi; Wu, Guo-sheng; Hao, Yan-hong; Feng, Jie; Li, Wen-ying
Highlights: CO2 recycle assistance with COG to CH3 OH with dry reforming is proposed. New process with dry reforming improves H2 utilization and energy saving. Process with H2 separation (CWHS) is more preferable to CH3 OH output. CWHS shows an excellent performance in energy, economy and CO2 emission reduction. Abstract: A process of CO2 recycle to supply carbon for assisting with coke oven gas to methanol process is proposed to realize clean and efficient coke oven gas utilization. Two CO2 recycle schemes with respect to coke oven gas, namely with and without H2 separation before reforming, are developed. It is revealed that the process with H2 separation is more beneficial to element and energy efficiency improvement, and it also presents a better techno-economic performance in comparison with the conventional coke oven gas to methanol process. The exergy efficiency, direct CO2 emission, and internal rate of return of the process with H2 separation are 73.9%, 0.69 t/t-methanol, and 35.1%, respectively. This excellent performance implies that reforming technology selection, H2 utilization efficiency, and CO2 recycle ways have important influences on the performance of the coke oven gas to methanol process. The findings of this study represent significant progress for future improvements of the coke oven gas to methanol process, especially CO2 conversion integrated with coke oven gas utilization in the coking industry.